Physiological response of cakul wader fish (Puntius binotatus) fed with pumpkin seed flour (Cucurbita moschata Durch) feed - Rivaldy Rama Budiman; Hany Handajani; Dony Prasetyo (IJOTA (Indonesian Journal of Tropical Aquatic), 2024)
The physiological condition and reproductive performance of fish are strongly influenced by feed quality and nutritional supplementation. Yellow pumpkin seed flour (*TBLK*) contains various nutrients and bioactive compounds that potentially improve fish physiological responses, growth, and reproductive development. Therefore, this study aimed to evaluate the effect of TBLK supplementation in feed on the physiological responses of cakul wader fish, including the Hepatosomatic Index (HSI), Viscerosomatic Index (VSI), Gonad Maturity Index (GMI), and survival rate. This study employed an experimental method using a Completely Randomized Design (CRD) with four treatments and three replications. The treatments consisted of commercial feed without supplementation (control), commercial feed supplemented with 2.5% TBLK, 5% TBLK, and 7.5% TBLK, each combined with 3% CMC as a binder. Fish with an average body weight of 4.9 ± 1.0 g were stocked at 25 fish per aquarium containing 25 L of water and reared for 40 days. Feeding was conducted twice daily using paste-form feed. The results showed that TBLK supplementation affected the physiological responses of cakul wader fish. The best performance was obtained at the 5% TBLK supplementation level, which produced the highest Gonad Maturity Index (0–5.81%) and survival rate (86.67%), while maintaining favorable HSI (1.29–1.93%) and VSI (2.44–3.93%) values. Lower survival rates were observed in the 2.5% (68%) and 7.5% (66.67%) treatments. In conclusion, supplementation of 5% TBLK in feed was the optimal dose for improving physiological condition, gonad maturation, and survival rate of cakul wader fish